Effect of response contingent negative stimulation on selected responses in a moment of stuttering - Viswanath NS (Journal of All India Institute of Speech and Hearing, 1972)
In recent years one can witness the increasing use of learning constructs andprinciples in the understanding and treatment of speech disorders. The problem ofstuttering comes to the forefront of one's attention in this respect The first comprehensivebook on stuttering with the behavioral-learning Orientation was writtenby Brutten and Shoemaker (1967). After critically examining the existing theoriesof stuttering which use learning constructs and principles (Sheehan, 1958; Wischner,1950; Shames and Sherick, 1963), Brutten and Shoemaker (1967), present the twofactor-theory of stuttering. Thus one of the criticisms levelled by them against thesetheoretical positions is that they cannot explain punishment data related to stutteringsatisfactorily. They point out that these theoretical positions generate theprediction that under punishing conditions the frequency of stuttering will decreasein accordance with the law of effect. The data they present leads them to the conclusionthat it is possibly true with regard to certain responses in a moment ofstuttering (tongue protrusion, foot tapping etc.) and not with others (repetitionsand prolongation of sounds and syllables). The latter responses increase in frequencywhen punished (Martin, et al. 1964).